Natural food ingredients from quince peel: Towards a "zero-waste" production system - Pereira, Alexis (2022)
The resources on our planet are finite and limited. Nonetheless, more and more waste is being produced worldwide. In this sense, it is essential to acquire circularity and "zero waste" approaches to move from the current environmentally unsustainable agri-food system to a more sustainable practice. Quince is the yellow fruit of the deciduous tree Cydonia oblonga Mill. This fruit has an intense aroma, flavor and acidity, but most varieties are too sour and astringent to be eaten raw, so it is usually processed into marmalade and many other food products, mostly sweets, through processes that discard the peel as a by-product. Therefore, this work was carried out to promote the upcycling of quince peel into valuable food ingredients following a "zero waste" approach. Thus, it was intended to optimize the extraction of compounds of interest to the food industry using the response surface methodology (RSM).